13C and 15N assimilation and organic matter translocation by the endolithic community in the massive coral Porites lutea. Issue 12 (6th December 2017) - Sangsawang, Laddawan; Casareto, Beatriz Estela; Ohba, Hideo; Vu, Hung Manh; Meekaew, Aussanee; Suzuki, Toshiyuki; Yeemin, Thamasak; Suzuki, Yoshimi
Abstract : Corals evolved by establishing symbiotic relationships with various microorganisms (the zooxanthellae, filamentous algae, cyanobacteria, bacteria, archaea, fungi and viruses), forming the 'coral holobiont'. Among them, the endolithic community is the least studied. Its main function was considered to be translocation of photo-assimilates to the coral host, particularly during bleaching. Here, we hypothesize that (i) endolithic algae may show similar primary production rates in healthy or bleached corals by changing their pigment ratios, and therefore that similar production and translocation of organic matter may occur at both conditions and (ii) diazotrophs are components of the endolithic community; therefore, N2 fixation and translocation of organic nitrogen may occur. We tested these hypotheses in incubation of Porites lutea with 13 C and 15 N tracers to measure primary production and N2 fixation in coral tissues and endoliths. Assimilation of the 13 C atom (%) was observed in healthy and bleached corals when the tracer was injected in the endolithic band, showing translocation in both conditions. N2 fixation was found in coral tissues and endolithic communities with translocation of organic nitrogen. Thus, the endolithic community plays an important role in supporting the C and N metabolism of the holobiont, which may be crucial under changing environmental conditions.